P-021 Safety and efficacy of balloon-assisted coil embolization of intracranial aneurysms: a single institution experience. (12th July 2011) - Santillan, A; Mazura, J; Riina, H; Gobin, Y; Patsalides, A
Abstract : Purpose: The safety of the balloon remodeling technique remains a matter of debate. In this report we analyze the safety of the balloon remodeling technique compared with coil embolization alone for the treatment of ruptured and unruptured intracranial aneurysms. Material and Methods: We retrospectively reviewed the medical records, procedures notes, and angiograms of 491 patients treated with coil embolization alone and the balloon remodeling technique from March 2002 to March 2010 at the Division of Interventional Neuroradiology at NYPH/Weill Cornell Medical Center. The aneurysms were classified in two groups according to the size of the aneurysm dome: 7 mm or less and larger than 7 mm. A wide-necked aneurysm was defined as a neck diameter >4 mm or a dome-to-neck ratio <1.5 mm. The adverse events were classified in three groups: thromboembolic events, intraprocedural ruptures, and device-related problems. Clinical outcomes of these adverse events were classified as none, transient or permanent neurologic deficit and death. Results: A total of 491 aneurysms (371 women, 120 men; mean age, 55.36±12.35 [SD]; range, 11–92 years) were embolized. 236 aneurysms were treated using the balloon remodeling technique, however; in 8 cases (3.4%) the balloon placement failed. Of the 491 treated aneurysms, 274 aneurysms (55.8%) presented with a previously ruptured aneurysm. 303 aneurysms (61.8%) measured 7 mm or less and 187 (38.2%) were larger than 7 mm. Dome-to-neck ratio was 1.5 or less in 169 (34.4%) and >1.5 in 322 patients (65.6%). Thromboembolic events, intraprocedural rupture, and device-related problems were encountered in 12 (2.4%), 19 (3.9%) and 16 (3.3%) patients respectively, for both treatment modalities. The rate of adverse events related to the balloon remodeling technique was seen in 26 cases (5.3%) compared to coil embolization alone that was 21 cases (4.3%). Patients treated with coil embolization alone were more likely to have a previously ruptured aneurysm compared to the balloon remodeling group (67.8% vs 42.8%). There was no statistical difference between both groups after treatment of aneurysms with a dome to neck ratio <1.5 (p=0.88, χ 2 test). The risk of thromboembolic events was the same in both groups (OR=0.92; 95% CI 0.29 to 2.91; p=0.89). A trend toward a lower risk of intraprocedural rupture was observed in the coil embolization group, but the results were not significant (OR=0.53; 95% CI 0.20 to 1.36; p=0.19). There was no statistical difference detected for the risk of device-related problems in both groups (OR=0.92; 95% CI 0.34 to 2.50; p=0.88). Conclusions: The balloon remodeling technique does not increase the risks of periprocedural complications associated with endovascular embolization of intracranial aneurysms.